Estimation Of Disharge Coefficient On Weir Configuration Based On Flow Rate And Velocity - Khusnita Azizah; Nurwahid Dimas Saputro; Budi Indra Setiawan; Allen Kurniawan (Applied Research on Civil Engineering and Environment (ARCEE), 2023)
The development of water treatment and water resources considers the flow rate adjusted using a weir. Weir is designed with many hydraulic factors, including the coefficient of discharge (Cd). Characteristics of the value of Cd show a decreasing trend on triangular and rectangular weirs. The value of Cd varies based on the flow's characteristics and the channel's geometry. Estimation of the best Cd value in flow discharge engineering and sediment deposition is necessary to know the accuracy of weir geometry. Some plans in water treatment and water resource building sometimes assume a Cd value based on literature. This study aims to estimate the value of Cd based on variations in flow rate and was conducted on a laboratory scale with weir shape limitations in the form of triangles and rectangles. The water sample was discharged by a water pump into an open channel. The angle of the weir opening was determined for the rectangular and triangular weir of 90°. Flow monitoring included flow discharge through the use of a current meter. Water was recycled in each measurement with a total of 60 cycles. The Cd values in a triangular weir were greater than in a rectangular weir. The Cd values for the rectangular weir ranged from 0.068 to 0.089, while the Cd values for the triangular weir ranged from 0.557 to 0.598. This value indicated that the greater the flow rate, the lower the Cd value. Therefore, weir configuration of water discharged using a triangular weir was better than a rectangular weir at low flow rates, less than 0.05 m3/s.